A comparative study of the Indonesia and Chinese educative systems concerning the dominant incentives to entrepreneurial spirit (desire for a new venturing) of business school students - Yang Kaijun; Puput Ichwatus Sholihah (Journal of Innovation and Entrepreneurship, 2015)
This study aims to analyze the influence of direct and indirect effect of the theory of planned behavior on entrepreneurial intention by using entrepreneurial education as an intervening variable. The study involved 109 students from Business School of Hohai University in China and 110 students from Business School of Brawijaya University in Indonesia. The data were obtained by using accidental sampling technique. In this case, the sample criteria were students that have taken up courses/seminars/training on entrepreneurship. Path analysis technique in this research was used by making use of existing software AMOS (Analysis of Moment Structure) version 18.00. The results of this study demonstrate the significance of subjective norm and perceived behavioral control to entrepreneurial education in Chinese students. Furthermore, this study also found indirect effect of perceived behavioral controls on entrepreneurial intention with entrepreneurial education as an intervening variable among Chinese students.
Keywords: 650; Theory of planned behavior; Entrepreneurial education and entrepreneurial intention